Developing an evaluation model based on unascertained measurement for evaluation of tunnel squeezing - Wei, Cong; Zhu, Shuangli; Chen, Chao; Zhou, Jian (Frontiers in Earth Science, 2022)
Tunnel squeezing brought great difficulties to the construction and even caused damage to construction workers. The research on large deformation evaluation methods has been widely developed, but the mechanism of large extrusion deformation is very complex, and the actual conditions of different tunnels are complex, so there is strong uncertainty in the prediction of squeezing tunnel. Therefore, we constructed an unascertained measure model incorporating four membership functions for evaluation of tunnel squeezing based on the existing two sets of data. Simultaneously, information entropy was introduced to objectively calculate the index importance for each factor. It is found that the unascertained measure model shows great potential on prediction of tunnel squeezing. For four different measure functions, the accuracy for the first set of data (GPI) is: 100%、83.33%、50% and 83.33%, respectively, and 70%、77.5%、67.5% and 70% for the second set of data (GPII). Additionally, Linear function and parabolic function can be considered as the reliable tool for uncertainty information interpretation The results revealed that the uncertainty model constructed in this study can enrich the available uncertainty evaluation system.